Computed Tomographic Evaluation of Pediatric Head Injury in Aminu Kano Teaching Hospital, Kano, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Objective:To describe the computerized tomographic findings in children with head trauma who presented at the Aminu Kano Teaching Hospital, Kano, Nigeria.Methods:It is a retrospective review of patients aged 9 month to 12 years with suspected head injury following head trauma, who presented for CT scan at Aminu Kano Teaching Hospital, Kano, Nigeria from January 2016 to December, 2017.Results:Sixty eight cases were reviewed retrospectively. They ranged from 9 months to 12 years with the mean age of 5 years. Fifty four (79.4%) were males. Fourteen were females (20.6%). Thirty five (51.5%) had head injury secondary to RTA. Twenty four (35.3%) had a history of fall from height. Four (5.9%) had a history of fall into a well. Four (5.9%) had a history of assault. Only one had a history of gun shot (1.5%). Twenty one patients (30.9%) had normal findings. Five (7.4%) of them had a frontal bone fracture. Seven (10.3%) had a parietal bone fracture. Two (2.9%) had fracture of base of the skull. Seventeen (25%) had intracerebral haematoma. Three had brain oedema (4.4%). One had epidural haematoma (1.5%). Eight (11.8%) had subdural haematoma. Six (8%) had combined fracture with cerebral contusion.Conclusion:RTA is a major cause of head injury in the most paediatric age group in our environment with CT scan as a valuable imaging tool in the investigation and management of these patients.